Los procesos de titulización de activos: Comentarios al precedente de observancia obligatoria emitido por la superintendencia del mercado de valores - Viale Leo, Miguel Antonio (2022)
Recently, in Peru, the SMV has issued a Mandatory Precedent in which some aspects referring to two securitization trusts have been questioned. This is because, from the SMV’s point of view, the securities issued against said trust assets had not met the requirements to be classified as transferable securities, in accordance with the regulations applicable to the case.The purpose of this article is to address certain aspects regarding asset securitization processes and the regulation that is applicable to them in the peruvian context.